MANAJEMEN BUDAYA LITERASI SEKOLAH DALAM PERSPEKTIF SOSIOLOGI PENDIDIKAN DI SD KENEP 01 SUKOHARJO - Sulistiyowati, Nourma Ayu; Sigit Haryanto; Definka Puan Shalika Abdillah; Mukhammad Sobirin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze school literacy culture management from the perspective of educational sociology in grades IV and V of SD Negeri Kenep 01 Sukoharjo. The research was motivated by the importance of literacy culture as a means of improving educational quality and as a social process involving interactions among school members. A qualitative approach with a case study design was employed to gain an in-depth understanding of literacy culture management within the school setting. The participants consisted of the principal, fourth- and fifth-grade teachers, and students selected through purposive sampling. Data were collected through semi-structured interviews, participant observation, and document analysis. Data trustworthiness was ensured through source triangulation, method triangulation, and member checking. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the school literacy culture is managed through five main programs: a 15-minute reading habit before class, classroom reading corners, students’ daily journals, scheduled library visits, and story sharing activities. These programs contributed to increased reading interest, improved writing skills, and better Indonesian language learning outcomes among students. The main supporting factors were the principal’s strong commitment and teachers’ active involvement, while limited funding and insufficient variety of reading materials were identified as major obstacles. The study demonstrates that literacy culture is a social construct developed through collaboration among all school stakeholders. The findings provide practical implications for developing more participatory and sustainable literacy policies and practices in elementary schools.